(untitled) (Journal of Health, Population and Nutrition, 2013)
Maternal mortality has been identified as a priority issue in health policy and research in India. The country, with an annual decrease of maternal mortality rate by 4.9% since 1990, now records 63,000 maternal deaths a year. India tops the list of countries with high maternal mortality. Based on a verbal autopsy study of 403 maternal deaths, conducted in 2008, this paper explores the missed opportunities to save maternal lives, besides probing into the socioeconomic factors contributing to maternal deaths in Jharkhand, India. This cross-sectional study was carried out in two phases, and a multistage sampling design was used in selecting deaths for verbal autopsy. Informed consent was taken into consideration before verbal autopsy. The analytical approach includes bivariate analysis using SPSS 15, besides triangulation of qualitative and quantitative findings. Most of the deceased were poor (89%), non-literates (85%), and housewives (74%). Again, 80% died in the community/at home, 28% died during pregnancy while another 26% died during delivery. Any antenatal care was received by merely 28% women, and only 20% of the deliveries were conducted by skilled birth attendants (doctors and midwives). Delays in decision-making, travel, and treatment compounded by ignorance of obstetric complications, inadequate use of maternal healthcare services, poor healthcare infrastructure, and harmful rituals are the major contributing factors of maternal deaths in India. J HEALTH POPUL NUTR 2013 Jun; 31(2): 262-271 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16391